Intravenous versus Partial Oral Antibiotic Therapy in the Treatment of Uncomplicated Bloodstream Infection Due to Streptococcus Species - Lynn E. Broermann; Majdi N. Al-Hasan; Sarah Withers; Kristina L. Benbow; Taylor Ramsey; Meghan McTavish; Hana R. Winders (Microorganisms, 2023)
This retrospective cohort study examines effectiveness of partial oral antibiotic regimens in uncomplicated bloodstream infections (BSIs) due to Streptococcus species compared to standard intravenous therapy. Adult patients with uncomplicated streptococcal BSIs from April 2016 to June 2020 in seven hospitals in South Carolina, USA, were evaluated. Multivariate Cox proportional hazards regression was used to examine the time to treatment failure within 90 days of a BSI after adjustment for the propensity to receive partial oral therapy. Multivariate linear regression was used to examine the hospital length of stay (HLOS). Among the 222 patients included, 99 received standard intravenous antibiotics and 123 received partial oral therapy. Of the standard intravenous therapy group, 46/99 (46.5%) required outpatient parenteral antibiotic therapy (OPAT). There was no difference in the risk of treatment failure between partial oral and standard intravenous therapy (hazards ratio 0.53, 95% CI 0.18, 1.60; p = 0.25). Partial oral therapy was independently associated with a shorter HLOS after adjustments for the propensity to receive partial oral therapy and other potential confounders (−2.23 days, 95% CI −3.53, −0.94; p < 0.001). Transitioning patients to oral antibiotics may be a reasonable strategy in the management of uncomplicated streptococcal BSIs. Partial oral therapy does not seem to have a higher risk of treatment failure and may spare patients from prolonged hospitalizations and OPAT complications.